Combined Resistance and Stretching Exercise Training Benefits Stair Descent Biomechanics in Older Adults - Gavin, James P.; Reeves, Neil D.; Jones, David A.; Roys, Mike; Buckley, John G.; Baltzopoulos, Vasilios; Maganaris, Constantinos N. (Frontiers in Physiology, 2019)
Introduction Stair descent is a physically demanding activity of daily life and common risk for falls. Age-related deteriorations in ankle joint capacities make stair descent particularly challenging for older adults in built environments, where larger rise steps are encountered. Exercise training may allow older adults to safely cope with the high biomechanical demands of stair descent. However, little is known about the demands of increased rise stairs for older adults, nor the impact of exercise. Aim We investigated whether the effects of lower-limb resistance training would alter joint kinetics and movement strategies for older adults when descending standard rise, and increased rise stairs. Method Fifteen older adults descended a four-step stair adjusted to standard rise (170 mm), and increased rise (255 mm) on separate visits. Between these two visits, randomly-allocated participants underwent 16 weeks of either: resistance exercise training (n=8) or habitual activity (n=7). Kinetic data were measured from step-mounted force plates, and kinematic data from motion-capture cameras. Training involved twice-weekly sessions of lower-limb resistance exercises (three sets of 8 repetitions at 80% three-repetition maximum), and static plantarflexor stretching (three, 45 s holds per leg). Results - Standard stairs Peak ankle joint moments increased (p<0.002) and knee joint moments decreased (p<0.01) during descent after exercise training. Peak centre of pressure-centre of mass (CoP-CoM) separations increased in posterior (p=0.005) and medio-lateral directions (p=0.04) after exercise training. Exercise training did not affect CoM descent velocity or acceleration. Increased rise stairs Required greater ankle, knee and hip moments (p<0.001), peak downwards CoM velocity and acceleration (p=0.0001), and anterior-posterior CoP-CoM separation (p=0.0001), but lower medial-lateral CoP-CoM separation (p<0.05), when compared to standard stair descent. Exercise training did not affect joint kinetics or movement strategies. Discussion Exercise training increased the maximum joint ROM, strength and force production of the ankle, and enabled a greater ankle joint moment to be produced in single-leg support (lowering phase) during standard stair descent. Descending increased rise stairs raised the task demand; exercise training could not overcome this. Future research should prioritise the ankle joint in stair descent, particularly targeting plantarflexor torque development across stairs of varying riser heights.